Interfacet distance at L4 is increased in spines with high‐pelvic incidence. Issue 8 (2nd April 2022) - Ren, Bryan O.; Teplensky, Jason R.; Abola, Matthew V.; Komarovsky, Michael B.; Cooperman, Daniel R.; Bauer, Jennifer M.; Liu, Raymond W.
Abstract: Pelvic incidence (PI) is an angular measurement linked to spinal pathologies. There is an increasing distance between facet joints moving caudally down the sagittal plane of the spine. We defined pedicle divergence (PD) as the ratio of interfacet distance (IFD) between adjacent levels. This study aimed to evaluate the relationship between PI and PD. Two hundred and thirty specimens were obtained from the Hamann‐Todd Osteological Collection. Specimens were catalogued for age, sex, race, PI, PD, and lumbar facet angle. Multivariate linear regression analysis was performed to determine the relationship between variables. IRB approval was not required. Average age at death was 57.0 years ±6.2 years. There were 211 (92%) male specimens and 176 (77%) were white. Average PI was 47.1 ± 10.5°. For PD between L3/L4, there was a relationship with PI ( β  = −0.18, p  = 0.008). For PD between L4/L5, there was an opposite relationship with PI ( β  = 0.21, p  = 0.003). Regression analyses of the interfacet to body ratio at each level found an association with PI only at L4 ( p  = 0.008). This study demonstrated that PI has a significant association with IFD in the lower lumbar spine. Increasing PI was associated with increased PD between L3/L4 and decreased PD between L4/L5. These results further support the close relationship between pelvic morphology and the lower lumbar spine, and suggest that L4 may have an important role in compensating for aberrant PI.